2022
DOI: 10.1177/15500594221136856
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Visual Inhibition in Amnestic Mild Cognitive Impairment

Abstract: Objective.The pathophysiology of amnestic mild cognitive impairment (aMCI) and Alzheimer disease (AD) is still a matter of debate. Visual system might be precociously altered, especially for its cholinergic connections. We thus studied patients with aMCI compared to AD with paired-pulse flash-visual evoked potentials (paired-F-VEPs), a putative marker of cholinergic function. Methods. We enrolled 12 adult patients with aMCI and 12 with AD. 14 normal age- and sex-matched subjects acted as controls (HS). Stimuli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
(61 reference statements)
0
1
0
Order By: Relevance
“…The main pathogenesis of AD involves cholinergic neuron dysfunction, with ash visual evoked potential (FVEP) P2 being associated with cholinergic function in the brain [20] . It has been shown that FVEP-P2 latency is prolonged in AD patients [21] . These ndings collectively con rm the presence of visual disturbances experienced by individuals with AD.…”
Section: Discussionmentioning
confidence: 99%
“…The main pathogenesis of AD involves cholinergic neuron dysfunction, with ash visual evoked potential (FVEP) P2 being associated with cholinergic function in the brain [20] . It has been shown that FVEP-P2 latency is prolonged in AD patients [21] . These ndings collectively con rm the presence of visual disturbances experienced by individuals with AD.…”
Section: Discussionmentioning
confidence: 99%